A Study on Organizational Change and the Reactions of Employees to It: Understanding employee reactions to organizational change (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Organizational change is necessary for businesses toremain competitive in today’s market. To successfully implement changeinitiatives, change agents must understand that the role of employees is highlyimportant, and employees’ reactions to change are influenced by a number of factors,including employees’ emotions and cognitions, communication, and participationin decision making. Change agents can apply the Spectrum of Employees’Reactions to Organizational Change as a unique model that illustrates howemployees react to change. This model is based in the concept that the degreeof employees’ acceptance of or resistance is an important factor that changeagents should examine. Overall, this paper provides OD practitioners importantinformation about employees’ reactions to change, and organizations willbenefit from further research in this field.